The Nature of Poverty : a case-history of the first quarter-century after World War II - Haswell, Margaret Rosary (London : Macmillan, 1975)
The nature of poverty in this context has been subjected to careful analysis to provide a basis for policy leading to its ultimate elimination as a constraint on development of the mental faculties and material well-being of societies so afflicted. The opportunity for study of the human scene in a particular community by the same core of researchers over a long span of years gives the work an authenticity of a unique character.
Includes bibliographical references p. 221-224 and index.
rpm 16/09/2016
Loans
Keywords: Agriculture; Food supply; Rural conditions; Poverty; Gambia